MiR-141-3p Relative Expression Level from FFPE Samples as Biomarker of Prostate Adenocarcinoma Carcinogenesis in Yogyakarta, Indonesia - Sari Eka Pratiwi; Sri Nuryani Wahyuningrum; Rachmagreta Perdana Putri; Danarto Danarto; Didik Setyo Heriyanto; Nur Arfian; Sofia Mubarika Haryana; Indwiani Astuti (Universitas Nahdlatul Ulama Surabaya, 2022)
Globally, prostate cancer (PCA) is the second leading cause of male cancer-associated mortality. Micro-RNAs (miRNAs) are small non-coding RNAs considered promising biomarkers for diagnosis, prognosis, and treatment options. A miR-141 expression is frequently dysregulated and influences the development and progression of PCA. This study aimed to identify miR-141 expression level as a marker to differentiate PCA from another prostate anomaly, especially in Yogyakarta. Formalin-fixed paraffin-embedded (FFPE) tissues for each three groups: benign prostatic hyperplasia/BPH, high-grade prostatic intraepithelial neoplasia/HGPIN, and PCA (n=7/group) were stored in a commercial clinical laboratory in Yogyakarta. The total RNA was extracted from FFPE sections using miRNeasy FFPE kit, followed by the quantification of miR-141-3p expression level by RT-PCR. The result showed that miR-141 relative expression level on PCA was higher than other groups and significantly different (P<0.05, Kruskal Wallis test). The mean of the miR-141 relative expression level of BPH, HGPIN, and PCA were 1.04±0.87, 6.44±7.8, and 7.06±8.83, respectively. The relative expression level of miR-141 can potentially be a prognostic biomarker in PCA and could differentiate aggressiveness in prostate anomaly, especially BPH, HGPIN, and PCA.